Prevalence and Causes of Blindness and Visual Impairment Among Nigerian Children: A Systematic Review - Eze UA; Obasuyi OC; Salihu DV; Bature M; Yeye-Agba OO; Kanmodi KK (Clinical Ophthalmology, 2024)
Ugochukwu Anthony Eze,1,2 Osamudiamen Cyril Obasuyi,3 Dora Valerie Salihu,4 Mustapha Bature,5,6 Olabisi Olayemi Yeye-Agba,7 Kehinde Kazeem Kanmodi8– 11 1Department of Ophthalmology, Federal Medical Centre, Asaba, Nigeria; 2School of Sciences, Health Sciences Technology Engineering University of Suffolk-Unicaf, Ipswich, UK; 3Department of Ophthalmology, Irrua Specialist Teaching Hospital, Irrua, Nigeria; 4Department of Ophthalmology, Garki Specialist Hospital, Abuja, Nigeria; 5Department of Ophthalmology, Usmanu Danfodiyo University, Sokoto, Nigeria; 6University Teaching Hospital, Sokoto, Nigeria; 7Department of Ophthalmology, Federal Teaching Hospital, Lokoja, Nigeria; 8School of Dentistry, University of Rwanda, Kigali, Rwanda; 9Faculty of Dentistry, University of Puthisastra, Phnom Penh, Cambodia; 10Cephas Health Research Initiative Inc, Ibadan, Nigeria; 11School of Life Sciences, Teesside University, Middleborough, UKCorrespondence: Kehinde Kazeem Kanmodi, School of Dentistry, University of Rwanda, Kigali, Rwanda, Email kanmodikehinde@yahoo.com Ugochukwu Anthony Eze, Department of Ophthalmology, Federal Medical Centre, Asaba, Nigeria, Email ugorexeze@gmail.comBackground: Low/middle-income countries have the highest burden of blindeness and visual impairment, which directly affects the children and indirectly affects their community. Furthermore, the number of blind years suffered by children with low vision or blindness creates a self-perpetuating ripple effect on their development, health and the socio-economic development of their communities. This systematic review aims to interrogate the existing evidence on the prevalence and causes of blindness and visual impairment in Nigerian children to provide evidence to drive health policy.Methods: This was a systematic review without meta-analysis (SwiM) using a narrative synthesis of the evidence reported using the PRISMA guidelines. All primary cross-sectional studies (in English) reporting the prevalence and causes of visual impairment among Nigerian children under 20 years old between 2003 and 2022 were included in this review. PUBMED, AJOL, BASE and ProQuest databases were searched for eligible studies between 6 June and 15 July 2023. The quality of the included studies was assessed using the AXIS tool. Results were extracted and summarised using descriptive statistics. Visual impairment and blindness using the presenting visual acuity in the better eye were reported using the WHO classification.Results: Seventeen studies, involving 16,924 children from 13 states across five geo-political zones in Nigeria, were included in the final analysis of this review. The prevalence of visual impairment was 3.9%, 2.7% and 0.3% for mild, moderate and severe visual impairments, respectively, due to ametropia, cataracts, glaucoma, etc. The prevalence of blindness was 0.2% due to cataracts, corneal scars and optic atrophy.Conclusion: Blindness and visual impairment is still a significant clinical and public health burden among Nigerian children. Hence, there is still a need for clinicians, especially opthalmologists, public health specialists, policy-makers, and other relevant stakeholders to intensify efforts towards the prevention and control of this burden.Keywords: visual impairment, blindness, childhood blindness, childhood visual impairment, Nigeria, systematic review